FAKTOR YANG MEMPENGARUHI IMPLEMENTASI PROGRAM KELUARGA HARAPAN (PKH) DI KECAMATAN POASIA KOTA KENDARI SULAWESI TENGGARA - Mesti Asnia; Mustakim Mustakim; Suryani BB (Universitas Halu Oleo, 2019)
This study aims to determine factors affecting implementation Hope family program (pkh) in poasia district Kendari City, Southeast Sulawesi. The approach of this research is a qualitative approach with descriptive qualitative research. The technique of collecting data is done through observation, interviews, and documentation. The data analysis technique used consists of data collection, data reduction, data presentation and conclusion drawing. The results of this study indicate that the implementation of the PKH policy in Poasia District, in general, has not been implemented properly based on PKH knowledge and socialization carried out by the facilitator; Validation process in determining PKH participants; The process of distributing PKH funds to PKH recipients is carried out through the channelling bank; The obligation of PKH participants to carry out their obligations has not been well understood; while the factors that influence the implementation of the program do not always affect. The conclusion of the study shows that the implementation of the Family Hope Program policy in Poasia District, in general, has not been implemented well.